Treatment of HBV HCV co-infection: exceeded response. - Barbosa, João (2011)
Hepatitis B (HBV) and hepatitis C (HCV) are the most common causes of chronic liver disease. Due to shared routes of transmission, co-infection with HBV and HCV is not uncommon. Higher rates of cirrhosis and hepatocelular carcinoma have been demonstrated in HBV/HCV co-infected patients. No treatment standard has been established for HBV/HCV co-infected patients. Treatment decisions must be made based upon identification of the dominant virus, usually HCV, thus patients should receive pegylated interferon alpha with ribavirin as for HCV monoinfection. Sustained virological response rates for HCV are broadly comparable with HCV monoinfected patients. There is limited information regarding the benefit of combination with nucleos(t)ide analogues. Treatment decisions may modify the complex interaction between HBV and HCV, as flares of the untreated virus may occur, namely with reactivation of HBV. The authors report a case of HBV/HCV co-infection, without a dominant profile, in which the treatment response exceeded expectations regarding the available evidence.